2011
DOI: 10.1016/s0929-6646(11)60037-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Geriatric Frailty in a Northern Taiwan Community

Abstract: In this study, the prevalence of frailty was from 11.0% to 14.9% by different criteria and methodology. Various correlates were independently associated with frailty status. It is suggested that intervention for frailty requires an interdisciplinary approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 27 publications
4
71
0
5
Order By: Relevance
“…We identified seven studies which reported pain outcomes in older people with frailty (table 1). One study was conducted in Canada 11,17 , one in Australia 18,19 , one in Finland 20 , two in Taiwan 13,21 , and two in Brazil 22,23 . The mean age of participants ranged from 71 years to 82 years (see table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified seven studies which reported pain outcomes in older people with frailty (table 1). One study was conducted in Canada 11,17 , one in Australia 18,19 , one in Finland 20 , two in Taiwan 13,21 , and two in Brazil 22,23 . The mean age of participants ranged from 71 years to 82 years (see table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies used questions from the SF-12 or SF-36 to assess pain 11,13,19,23 . Chang et al 21 reported the presence of pain history but did not report the specific measure. The Geriatric Multidisciplinary Strategy for the Good Care of the Elderly (GeMS) study investigated the presence and severity of musculoskeletal pain, and chronicity 20 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study in northern Taiwan, for example, showed a slight difference in the prevalence of frailty in older adults, aged 65 to 79 years, using different instruments: the prevalence of frailty was 11.3% (95% CI: 7.6-15.0) using the Fried Frailty Index and 14.9% (95% CI: 10.7 to 19.1) using EFS (14) . The prevalence of frailty in this study was higher than that found in the same age group, using the EFS.…”
Section: Discussionmentioning
confidence: 99%